Factors That Influence the Quality of Financial Reports in UMKM in Surakarta - Ari Putra Andita; Eskasari Putri (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine the factors that influence the quality of financial reports in MSMEs in Surakarta. The research method used is quantitative. The test used in this study is a multiple regression test using SPSS. The data used is primary data with a sample of 102 MSMEs in Surakarta. The results of the study indicate that education level has a significant effect on the quality of MSME financial reports. Educational background does not have a significant effect on the quality of MSME financial reports. Business size does not have a significant effect on the quality of MSME financial reports. Length of business has a significant effect on the quality of MSME financial reports. Information technology has a significant effect on the quality of MSME financial reports.